An Initial Study of Neural Responses to Monetary Incentives as Related to Treatment Outcome in Cocaine Dependence - Jia, Zhiru; Worhunsky, Patrick D.; Carroll, Kathleen M.; Rounsaville, Bruce J.; Stevens, Michael C.; Pearlson, Godfrey D.; Potenza, Marc N. (Biological psychiatry (1969), 2011)
Although cocaine dependence (CD) involves abnormalities in drug-related, reward-based decision making, it is not well understood whether these abnormalities generalize to nondrug-related cues and rewards and how neural functions underlying reward processing in cocaine abusers relate to treatment outcome. Twenty CD patients before treatment and 20 matched healthy control (HC) subjects participated in functional magnetic resonance imaging while performing a monetary incentive delay task. Outcomes through 8 weeks were assessed via percent cocaine-negative urine toxicology, self-reported cocaine abstinence, and treatment retention. Among the whole sample, anticipation of working for monetary reward (i.e., reward anticipation) was associated with activation in the ventral striatum (VS), medial frontal gyrus, thalamus, right subcallosal gyrus, right insula, and left amygdala. Cocaine dependence compared with HC participants exhibited greater activation during notification of rewarding outcome (i.e., reward receipt) in left and right VS, right caudate, and right insula. In CD participants during reward anticipation, activation in left and right thalamus and right caudate correlated negatively with percent cocaine-negative urine toxicology, activation in thalamus bilaterally correlated negatively with self-reported abstinence measures, and activation in left amygdala and parahippocampal gyrus correlated negatively with treatment retention. During reward notification, activation in right thalamus, right VS, and left culmen correlated negatively with abstinence and with urine toxicology. These findings suggest that in treatment-seeking CD participants, corticolimbic reward circuitry is relatively overactivated during monetary incentive delay task performance and specific regional activations related to reward processing may predict aspects of treatment outcome and represent important targets for treatment development in CD.